Association of neopterin as a marker of immune system activation and juvenile rheumatoid arthritis activity - Mones M. Abu Shady; Hanan A. Fathy; Alaa Ali; Eman R. Youness; Gihan A. Fathy (Elsevier, 2015)
Objective: To evaluate neopterin plasma concentrations in patients with active juvenile idiopathic arthritis (JIA) and correlate them with disease activity. Methods: Sixty patients diagnosed as active JIA, as well as another 60 apparently healthy age- and gender-matched children as controls, were recruited from the Pediatrics Allergy and Immunology Clinic, Ain Shams University. Disease activity was assessed by the Juvenile Arthritis Disease Activity Score 27 (JADAS-27). Laboratory investigations were performed for all patients, including determination of hemoglobin concentration (Hgb), erythrocyte sedimentation rate (ESR), and C-reactive protein. Serum concentrations of tumor necrosis factor-alpha (TNF-α), interleukin-6 (IL-6), monocyte chemoattractant protein-1 (MCP-1), and neopterin were measured. Results: Significant differences were found between JIA patients and controls with regard to the mean levels of Hgb, ESR, TNF-α, IL-6, and MCP-1 (p < 0.05). A statistically significant higher mean level serum neopterin concentration (p < 0.05) was found in JIA patients (20.43 ± 8.73 nmol/L) than in controls (6.88 ± 2.87 nmol/L) (p < 0.05). Positive significant correlations were detected between serum neopterin and ESR, TNF-α, IL-6, MCP-1, and JADAS-27 (p < 0.05). No correlation was found between serum neopterin and CRP (p > 0.05). Multiple linear regression analysis showed that JADAS- 27 and ESR were the main variables associated with serum neopterin in JIA patients (p < 0.05). Conclusion: The elevation of plasma neopterin concentrations in early JIA patients may indicate stimulation of immune response. Serum neopterin can be used as a sensitive marker for assaying background inflammation and disease activity score in JIA patients. Resumo: Objetivo: avaliar as concentrações plasmáticas de neopterina em pacientes com artrite idiopática juvenil (AIJ) ativa e correlacioná-las com a atividade da doença. Métodos: Sessenta pacientes diagnosticados com AIJ ativa, bem como outras 60 crianças aparentemente saudáveis com a mesma idade e sexo no grupo de controle, foram recrutados da clínica de Alergia e Imunologia Infantil da Universidade Ain Shams. A atividade da doença foi avaliada pelo Escore de Atividade da Doença da Artrite Juvenil em 27 Articulações (JADAS-27). Foram realizadas investigações laboratoriais em todos os pacientes, incluindo a determinação da concentração de hemoglobinas, a taxa de sedimentação de eritrócitos e a proteína C-reativa. Foram mensuradas as concentrações séricas do fator de necrose tumoral alfa, interleucina-6 e proteína quimiotática de monócitos-1 e neopterina. Resultados: Foi encontrada uma diferença significativa entre os pacientes com AIJ e os controles quanto às médias de Hb, TSE, FNT-α, IL-6 e MCP-1 (p < 0,05). Foi encontrado um nível estatística e significativamente maior de concentração média de neopterina sérica (p < 0,05) em pacientes com AIJ (valor médio de 20,43 ± 8,73 nmol/L) que em controles (valor médio de 6,88 ± 2,87 nmol/L) (p < 0,05). Foram detectadas correlações positivas significativas entre a neopterina sérica e a TSE, FNT-α, IL-6, MCP-1 e JADAS-27 (p < 0,05). Não foi encontrada nenhuma correlação entre a neopterina sérica e a PCR (p > 0,05). A análise de regressão linear múltipla mostrou que o JADAS-27 e a TSE foram as principais variáveis associadas à neopterina sérica em pacientes com AIJ (p < 0,05). Conclusão: A elevação das concentrações plasmáticas de neopterina em pacientes com AIJ precoce pode indicar um estímulo de resposta imune. A neopterina sérica pode ser usada como um indicador sensível para analisar o histórico de inflamações e o escore de atividade da doença em pacientes com AIJ. Keywords: MCP-1, TNF-α, Rheumatoid arthritis, Palavras-chave: MCP-1, FNT-α, Artrite reumatoide